Perencanaan Pengelolaan Sarana dan Prasarana Pendidikan untuk Meningkatkan Kwalitas Pembelajaran di MTsN 9 Agam - Eriyanti Eriyanti; Yusmanidar Yusmanidar; Asmendri Asmendri; Milya Sari (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2024)
Planning is a process of describe an activities that will be done later in order to achieve the goals that have been set. In the world of education, planning of facilities and infrastructure is very necessary in improving the quality of student learning. Facilities are tools or facilities that are used directly in an activity, while infrastructure is the physical structure and basic facilities that support the operation of these facilities. The method used in this study is descriptive qualitative, including field surveys, interviews with stakeholders, and analysis of data from various sources. The results of the study indicate that complete and advanced facilities and infrastructure have a positive correlation with improving the quality of learning and improving students' abilities in achieving learning goals. This study concludes that investment in planning and managing facilities and infrastructure is a priority for Madrasahs in improving educational progress.